Characterizing, Assessing, and Treating Cognitive Dysfunction in Major Depressive Disorder. Issue 5 (September 2018) - McIntyre, Roger S.; Lee, Yena; Carmona, Nicole E.; Subramaniapillai, Mehala; Cha, Danielle S.; Lee, JungGoo; Lee, Jae-Hon; Alageel, Asem; Rodrigues, Nelson B.; Park, Caroline; Ragguett, Renee-Marie; Rosenblat, Joshua E.; et al.
Abstract : Learning objectives: After participating in this activity, learners should be better able to: Characterize cognitive dysfunction in patients with major depressive disorder. Evaluate approaches to treating cognitive dysfunction in patients with major depressive disorder. Abstract: Cognitive dysfunction is a core psychopathological domain in major depressive disorder (MDD) and is no longer considered to be a pseudo-specific phenomenon. Cognitive dysfunction in MDD is a principal determinant of patient-reported outcomes, which, hitherto, have been insufficiently targeted with existing multimodal treatments for MDD. The neural structures and substructures subserving cognitive function in MDD overlap with, yet are discrete from, those subserving emotion processing and affect regulation. Several modifiable factors influence the presence and extent of cognitive dysfunction in MDD, including clinical features (e.g., episode frequency and illness duration), comorbidity (e.g., obesity and diabetes), and iatrogenic artefact. Screening and measurement tools that comport with the clinical ecosystem are available to detect and measure cognitive function in MDD. Notwithstanding the availability of select antidepressants capable of exerting procognitive effects, most have not been sufficiently studied or rigorously evaluated. Promising pharmacological avenues, as well as psychosocial, behavioral, chronotherapeutic, and complementary alternative approaches, are currently being investigated.